PENGARUH PRODUK, HARGA, LOKASI, DAN PROMOSI TERHADAP KEPUASAAN KONSUMEN DENGAN PERUSAHAAN UNILEVER LEWAT DIGITAL MARKETING - Indrasto Kurniadi (Bajang Institute, 2025)
This study examines how marketing strategies, encompassing product, price, distribution, and promotion, influence consumer satisfaction with Unilever products, particularly within the context of digital marketing. In today's era of digital transformation, companies are required to adapt to technological developments and increasingly active consumer behavior on digital platforms. Unilever, as a multinational consumer goods company, employs various digital marketing strategies to reach and retain its customers. Through a quantitative approach and analysis of data from respondents who are active online Unilever consumers, this study found that all marketing variables—product, price, distribution, and promotion—have a significant impact on consumer satisfaction. The results also indicate that creative digital promotions and consistent product quality are dominant factors in shaping customer loyalty and satisfaction. The influential factor: promotion 0.341, F-test 13.771. This abstraction provides an overview of the importance of synergy between classic marketing strategies and digital innovation to maintain a company's relevance and competitive advantage in the modern marketplace.